IoT based home automation system / Iffah Afifah Nazurah Matsud - Matsud, Iffah Afifah Nazurah (2024)
The IoT Based Home Automation System presents a comprehensive solution for remote monitoring and control of home appliances using Internet of Things (IoT) technologies. This project aims to enhance convenience, efficiency, and security in households by integrating various sensors, microcontrollers, and communication protocols. Through the implementation of ESP32 microcontroller, along with sensors such as LDR, DHT11, and IR, the system enables real-time monitoring of environmental parameters like light intensity, temperature, and motion detection. The Blynk platform facilitates remote control and monitoring via a user-friendly mobile application. The project encompasses several phases, including breadboard circuit testing, PCB layout design, and prototype development. Challenges such as soldering issues and component malfunctions were encountered during the testing phase, underscoring the importance of thorough quality assurance procedures. Recommendations for future enhancements include refining PCB design, exploring additional sensors for enhanced functionality, and optimizing user interface for improved usability. Overall, the IoT Based Home Automation System demonstrates the potential of IoT technologies to revolutionize home automation, providing users with greater convenience, efficiency, and peace of mind.